A Dynamic Urban Lake Area Evolution Model Based on Multilevel Grid, Cellular Automata, and Multiagent System. (17th September 2020) - Zhu, Jianfeng; Tian, Shenzhen
Abstract : Urban lakes have been threatened by rapid expansion of cities in recent years. Their area changes could be extracted by remote sensing technologies. On this basis, a Dynamic Urban Lake Area Evolution Model (DULAEM) is proposed based on a multiagent system (MAS) and a cellular automata (CA) model. The DULAEM is integrated upon an Urban Lake Multilevel Grid (ULMG), which is composed of the vector model with the raster model. In the DULAEM, the CA layer is mainly used for modelling the interactions between urban lakes and their surrounding land use change through the activity of each cell; the MAS layer represents the actions of three typical human activities: government, real estate developers, and residents. These three agents have different actions in extent, strength, and priority according to their standpoints and functions. The CA layer and the MAS layer are both integrated upon the ULMG. Finally, a case study in Wuhan proves that the DULAEM can control the global relative error under 10%. Therefore, the DULAEM is able to simulate the area change of urban lakes dynamically. It is significant for the policy-making of lake protection and the optimal configuration of land resources in the lakeside.